Exploring Pre-Laboratory Engagement in Higher Education through a Validated Qualitative Approach - Chavez, John C.; Namoco, Sarah O. (Asian Journal of Applied Education (AJAE), 2025)
This qualitative study explored how higher education TVET students and instructors engage during pre-laboratory idle time, a phase often overlooked in laboratory-based instruction. Guided by Engagement Theory and Self-Determination Theory, data were gathered through semi-structured interviews, non-participant observations, and institutional documents in two Philippine state universities. Interview protocols were pre-tested through cognitive interviews to ensure clarity, construct alignment, and contextual fit. Thematic analysis revealed four themes: proactive behavior and routine, instructor presence, emotional and motivational tensions, and environmental and institutional influences. Results show that idle time can foster readiness, self-regulation, and collaboration when supported by clear expectations, instructor visibility, and enabling environments. The study highlights the value of structuring idle time as a vital component of TVET pedagogy.